Screening of entomopathogenic fungi against citrus mealybug (Planococcus citri (Risso)) and citrus thrips (Scirtothrips aurantii (Faure)) - FitzGerald, Véronique Chartier (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2014)
Mealybugs (Planococcus citri) and thrips (Scirtothrips aurantii) are common and extremely damaging citrus crop pests which have proven difficult to control via conventional methods, such as chemical pesticides and insect growth regulators. The objective of this study was to determine the efficacy of entomopathogenic fungi against these pests in laboratory bioassays. Isolates of Metarhizium anisopliae and Beauveria bassiana from citrus orchards in the Eastern Cape, South Africa were maintained on Sabouraud Dextrose 4% Agar supplemented with Dodine, chloramphenicol and rifampicin at 25Â°C. Infectivity of the fungal isolates was initially assessed using 5th instar false codling moth, Thaumatotibia leucotreta, larvae. Mealybug bioassays were performed in 24 well plates using 1 x 107 ml-1 conidial suspensions and kept at 26Â°C for 5 days with a photoperiod of 12 L:12 D. A Beauveria commercial product and an un-inoculated control were also screened for comparison. Isolates GAR 17 B3 (B. bassiana) and FCM AR 23 B3 (M. anisopliae) both resulted in 67.5% mealybug crawler mortality and GB AR 23 13 3 (B. bassiana) resulted in 64% crawler mortality. These 3 isolates were further tested in dose-dependent assays. Probit analyses were conducted on the dose-dependent assays data using PROBAN to determine LCâ‚…â‚€ values. For both the mealybug adult and crawlers FCM AR 23 B3 required the lowest concentration to achieve LCâ‚…â‚€ at 4.96 x 10â ¶ conidia ml-1 and 5.29 x 10â µ conidia ml-1, respectively. Bioassays on adult thrips were conducted in munger cells with leaf buds inoculated with the conidial suspensions. Isolate GAR 17 B3 had the highest mortality rate at 70% on thrips while FCM AR 23 B3 resulted in 60% mortality. Identification of the isolates, FCM AR 23 B3, GAR 17 B3 and GB AR 23 13 3, were confirmed to be correct using both microscopic and molecularly techniques. ITS sequences were compared to other sequences from GenBank and confirmed phylogenetically using MEGA6. Mealybug infection was investigated using scanning electron microscopy, mycosis was confirmed but the infection process could not be followed due to the extensive waxy cuticle. These results indicate that there is potential for the isolates FCM AR 23 B3 and GAR 17 B3 to be developed as biological control agents for the control of citrus mealybug and thrips. Further research would be required to determine their ability to perform under field conditions.
Keywords: Entomopathogenic fungi; Citrus mealybug -- South Africa -- Eastern Cape; Citrus thrips -- South Africa -- Eastern Cape; Citrus -- Diseases and pests; Citrus mealybug -- Biological control; Citrus thrips -- Biological control; Biological pest control agents; Scanning electron microscopy; Mycoses